Are humans by birth as wicked as the Heidelberg Catechism (3-11) holds? A dialogue between theology and modern sciences - P. Lampe (Acta Theologica)
While the introduction compares the Heidelberg Catechism’s theologically framed concept of sin with similar and opposing secular views of the past (e.g., Plautus, Quintilian, Hobbes), the main part uses contemporary scientific studies to challenge the Catechism’s view that (after alienation from God in the Fall) all human individuals by birth are wicked: incapable of loving others. Studies discovered remarkable capacities of empathy and altruism already in young children of different cultures as well as in primates, suggesting that altruism is deep-rooted in common ancestors of humans and primates. However, humans encounter limits of their capacity for altruism especially when dealing with outsiders not belonging to their own group. Culture, especially religion, is needed to advance a systematic, and not just spontaneous, altruism reaching beyond one’s group boundaries. Concluding remarks, using Paul, roughly sketch what a modern harmatiology would have to emphasize if it is not moral corruptness.